Ecological Design of the Urban Environment - Norbaeva M.; Vetlugina, A.V. (Genius Journals, 2022)
The process of urbanization contributes to the increase of production activity in many areas, while simultaneously solving social and cultural-educational problems of society. In this article, the issues of the ecologization and ecologiс design of settlements of various sizes to ensure their sustainable development are considered.
Keywords: Sustainable; development; settlements; green spaces